N-Acetyl-l-cysteine enhances ex-vivo amplification of deciduous teeth dental pulp stem cells. (October 2016) - Debeljak Martacic, Jasmina; Borozan, Suncica; Radovanovic, Anita; Popadic, Dusan; Mojsilovic, Slavko; Vucic, Vesna; Todorovic, Vera; Kovacevic Filipovic, Milica
Highlights: N -Acetyl-l -cysteine (NAC) has an effect on the cell fate that is dependent on the cell type and NAC dose applied. The lowest NAC dose (0.1 mM) stimulated DTSC proliferation, while the highest dose (2 mM) inhibited. The lowest NAC dose (0.1 mM) stimulated entry of DTSC into S phase of cell cycle. The lowest NAC dose (0.1 mM) exerted significant positive effect on DTSC antioxidative defense. All tested NAC concentrations (0.1 mM, 1.0 mM, 2.0 mM) stimulated DTSC osteo-chondrogenesis. Abstract: Objective: Obtaining high number of stem cells is of interest for cell based therapies. N -Acetyl-l -cysteine (NAC) acts as a source of sulfhydryl groups and an anti-oxidative agent. The aim of this study was to test different NAC concentration on proliferation and differentiation of deciduous teeth dental pulp stem cells (DTSCs) in vitro as well as to define the possible underlining mechanism of its effect. Design: Number of viable, apoptotic and senescent DTSCs was determined after addition of NAC (0.1 mM, 1.0 mM, 2.0 mM). Also, cell cycle analysis, HIF1-α expression, LDH isoenzymes, superoxide-dismutase (SOD) and catalase (CAT) activity, sulfhydryl groups content, the level of lipids' and proteins' oxidative damage and differentiation capacity of NAC treated DTSCs was determined. Results: DTSCs expressed HIF-1α in all conditions. The lowest NAC dose (0.1 mM) increased the number of DTSCs by one fifth comparing to the control, most likely stimulating entry of cells into S phase of cell cycle and enhancing the activity of LDH5 isoenzyme. The highest NAC dose (2 mM) inhibited DTSCs proliferation. Also, DTSCs had the lowest level of oxidative damage with 0.1 mM NAC. All tested NAC concentrations enhanced DTSCs osteo-chondrogenesis. Conclusion: The lowest NAC dose exerted significant positive effect on DTSCs proliferation as well as antioxidative protection creating beneficial environment for stem cells in vitro cultivation especially when their clinical use is important for stimulation of osteo-chondrogenesis.